The emigrant prose of S.D. Dovlatov in the context of American ‘new journalism’ of the 1980s - Evgeniya Yu. Poselenova; Victoriya S. Monsh (RUDN Journal of Studies in Literature and Journalism)
The focus of research attention is concentrated on the features of the American ‘new journalism’ of the 1960s-80s, and the influence of its narrative and stylistic techniques on the prose and journalism of S.D. Dovlatov during the emigrant period of his work. The problem is to study the collections “Compromise” and “Speech for no reason... or Editor’s columns” in the context of the ‘new journalism’ in the USA, identifying the specific methods and techniques of this phenomenon used by Dovlatov. The authors of the article, based on Dovlatov’s immersion in the context of new American journalism and the proximity of its creative views to the principles put forward by T. Wolfe and his environment, consistently trace the influence of ‘new journalism’ on poetics of the emigrant collections. One of the key features of the new American journalism was desire to present reliable information using artistic techniques, thereby not only changing reader’s perception of the materials, but making them even more capable of eliciting a strong emotional response. As a result of the analysis of Dovlatov’s selected collections, some techniques and features of the ‘new journalism’ were discovered: the real basis of the plot; narration on behalf of a character associated with the personality of the author; dialogue; composite installation; details; internal monologue and specific punctuation. The use of these tools allowed Dovlatov not only to create the effect of the reliability of what is happening, but also to demonstrate the author’s position, entering into an indirect dialogue with the reader.